On Stability of $L$-Fuzzy Mappings with Related Fixed Point Results (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, a general idea of Presic type $L$-fuzzy fixed pointresults using some weakly contractive conditions in the setting of metric spaceis initiated. Stability of $L$-fuzzy mappings and associated new concepts areproposed herein to complement their corresponding notions related to crispmulti-valued and single-valued mappings. Illustrative nontrivial examples areprovided to support the assertions of our main results.
Keywords: $L$-fuzzy set; $L$-fuzzy fixed point; metric space; multi-valued mapping; stability.